Optimal consumption for recursive preferences with local substitution: The case of certainty - Hanwu Li; Frank Riedel; Shuzhen Yang (Bielefeld University, Center for Mathematical Economics (IMW), 2022)
We characterize optimal consumption policies in a recursive intertemporal utility framework with local substitution. We establish existence and uniqueness and a version of the Kuhn-Tucker theorem characterizing the optimal consumption plan. An explicit solution is provided for the case when the felicity function is of the Epstein-Zin's type.
urn:nbn:de:0070-pub-29670569
Keywords: C61; D11; D81; G11; 330; Recursive utility; Hindy-Huang-Kreps preference; Intertemporal Substitution; Utility maximization